Formulación de una política pública relacionada con la presencia de vendedores ambulantes en los alrededores de los establecimientos de educación primaria del centro de la ciudad de Loja, durante el primer trimestre 2019 - González Luzuriaga, Karina Elizeth (2019)
This research entitled: "Formulation of a public policy related to the presence of street vendors in the vicinity of primary education establishments in the center of the city of Loja, during the first quarter of 2019", aims to explain an alternative solution in the language of public policies, through the construction of a problem and a solution consisting of a Comprehensive Coexistence Program composed of: Plan 1. Cooperation for human rights; Plan 2. Coexistence training; and Plan 3. Generate sources of employment. Program that tries to solve problematic relationships that the violence implies, as a result of the urgent and serious prioritization exercise of each one of the problems generated by the presence of street vendors around the schools of downtown Loja. Of the three plans proposed in the comprehensive coexistence program, Plan 3 is explained: Generate Employment Sources, through the creative entrepreneurship of the street vendor, which could become an interesting productive alternative for job creation in terms of productive, labor organization and business for the development of the city of La Loja. The survey instrument and the direct observation method were used to achieve the objectives of this research work.